1996
DOI: 10.1111/j.1469-8137.1996.tb01861.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated carbon dioxide and arbuscular mycorrhizal infection onTrifolium repens

Abstract: SUMMARYTrifolium repens L. cv. aran was grown for 58 d at ambient (350//mol moi"^) and elevated (700//moi mol"') atmospheric CO^, with and without the arbuscular mycorrhizal fungus Glo?nus mosseae (Nicol. & Gerd.) Gerd. & Trappe cv. YV. Plant biomass, mycorrhizal infeciion, non-structural carbohydrates, C, N and P content were examined. Ele\'ated CO., (a) significantly increased above-and below-ground biomass, (b) decreased specific leaf area and specific root lengtb, (c) decreased tissue "^N and increased tbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 48 publications
3
37
1
2
Order By: Relevance
“…The greater percentage of root length colonized in P. lanceolata under C ELEV contrasts with the situation reported not only for T. repens by Jongen et al (1996) but also for other C $ plants : Gossypium , Pascopyrum (Monz et al, 1994), Artemisia (Klironomos et al, 1996) and Liriodendron (O'Neill et al, 1991). Sequential harvests in the latter study revealed progressive increases in total root length with time without change in the proportion of colonized to non-colonized root.…”
Section: contrasting
confidence: 48%
See 3 more Smart Citations
“…The greater percentage of root length colonized in P. lanceolata under C ELEV contrasts with the situation reported not only for T. repens by Jongen et al (1996) but also for other C $ plants : Gossypium , Pascopyrum (Monz et al, 1994), Artemisia (Klironomos et al, 1996) and Liriodendron (O'Neill et al, 1991). Sequential harvests in the latter study revealed progressive increases in total root length with time without change in the proportion of colonized to non-colonized root.…”
Section: contrasting
confidence: 48%
“…In addition to the inherent genotypic differences between the species, the fact that the former study used a higher CO # concentration and a distinctive nutrient regime might have contributed to the different response. Jongen et al (1996) found that elevated CO # treatment caused no increase in the proportion of total root length of T. repens that was colonized at 58 d, and even found reduced colonization which was smaller than that seen in P. lanceolata at 41 d. However, subsequent harvests of P. lanceolata demonstrated an increasingly large influence of C ELEV on colonization, to the extent that by 104 d in this treatment the mycorrhizal root length was four times that seen in C AMB . It was a feature of the present study that most of the differences between M plants exposed to CO # treatment only became apparent at 76 d, these effects becoming progressively more pronounced towards the final harvest.…”
Section: mentioning
confidence: 89%
See 2 more Smart Citations
“…However, only one study has been performed that examines the response of mycorrhiza to elevated CO # using symbiotic N # -fixing plant species (Jongen et al, 1996). Elevated CO # has been shown to stimulate the productivity of symbiotic N # -fixing plants (Norby, 1987 ;Arnone & Gordon, 1990 ;Thomas et al, 1991 ;Tissue et al, 1997 ;Vogel et al, 1997).…”
mentioning
confidence: 99%